# Simplify: (3x + 2y)² - (3x - 2y)²

**Solution:**

Given, (3x + 2y)² - (3x - 2y)²

Using standard __identities__: (a + b)² = a² + 2ab + b² and (a - b)² = a² - 2ab + b²

Here, a = 3x and b = 2y

(3x + 2y)² - (3x - 2y)²

= [(3x)² + 2(3x)(2y) + (2y)²] - [(3x)² - 2(3x)(2y) + (2y)²]

= [9x² + 12xy + 4y²] - [9x² - 12xy + 4y²]

= 9x² - 9x² + 12xy + 12xy + 4y² - 4y²

= 24xy

**✦ Try This:** Simplify: (7p + 4q)² - (7p - 4q)²

Given, Simplify: (7p + 4q)² - (7p - 4q)²

Using standard identities: (a + b)² = a² + 2ab + b² and (a - b)² = a² - 2ab + b²

Here, a = 7p and b = 4q

= [(7p)² + 2(7p)(4q) + (4q)²] - [(7p)² - 2(7p)(4q) + (4q)²]

=49p² + 56pq + 16q² - 49p² + 56pq - 16q²

= 112pq

**☛ Also Check: **NCERT Solutions for Class 8 Maths Chapter 9

**NCERT Exemplar Class 8 Maths Chapter 7 Problem 84(ii)**

## Simplify: (3x + 2y)² - (3x - 2y)²

**Summary:**

Simplifying (3x + 2y)² - (3x - 2y)² we get, 24xy

**☛ Related Questions:**

visual curriculum